Spatial Capabilities Through The Auditory Kinesthetic Visualization Self Regulated Learning Model In The Covid-19 Era - Lilis Saputri; Mardiati Mardiati; Dewi Rulia Sitepu; Khairina Afni (Ridwan Institute, 2022)
The purpose of this study was to describe the answer process made by students in solving spatial ability questions through the Visualization Auditory Kinesthetic (VAK) learning model in the Covid-19 era. This type of research was conducted using a qualitative case study method on students' spatial abilities. The sample in this study was seventh-grade junior high school students from the purposive sampling technique and was taken by the initial screening results. The instruments used in data collection are observation and documentation. The results of this study indicate that spatial abilities through the Visualization Auditory Kinesthetic (VAK) learning model students can better understand the material because this model is better able to understand the material with their respective learning styles. The spatial ability consists of orientation, mental rotation, visualization, perception, relation, and disembedding. It turned out that many students answered correctly with a complete answer process on aspects of orientation, visualization, and perception. The rest on aspects of mental rotation, relation, and disembedding, there are still some students who have not answered correctly, and the answer process is complete. Therefore, it should be noted that aspects that cannot be answered correctly need improvements in the learning process or in questions that support aspects of mental rotation, relation, and disembedding spatial abilities to understand the geometry material better